2019
DOI: 10.1007/s10863-019-09800-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as a possible target for nicotine action

Abstract: Mitochondria are multifunctional and dynamic organelles deeply integrated into cellular physiology and metabolism. Disturbances in mitochondrial function are involved in several disorders such as neurodegeneration, cardiovascular diseases, metabolic diseases, and also in the aging process. Nicotine is a natural alkaloid present in the tobacco plant which has been well studied as a constituent of cigarette smoke. It has also been reported to influence mitochondrial function both in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 132 publications
(201 reference statements)
2
42
0
2
Order By: Relevance
“…Consistent with these findings, it was reported that COVID-19 may be more fatal in the elderly-population than in children, as with increasing the age, there is a gradual decline in the cellular ATP and subsequent ATP-induced cAMP accumulation (Srivastava, 2017). Furthermore, tobacco smokers, who suffer from a decreased content of ATP in immune cells, are also found to be more susceptible for COVID-19 infection (Malińska et al, 2019).…”
Section: Et-1-reduced Camp In Covid-19supporting
confidence: 53%
“…Consistent with these findings, it was reported that COVID-19 may be more fatal in the elderly-population than in children, as with increasing the age, there is a gradual decline in the cellular ATP and subsequent ATP-induced cAMP accumulation (Srivastava, 2017). Furthermore, tobacco smokers, who suffer from a decreased content of ATP in immune cells, are also found to be more susceptible for COVID-19 infection (Malińska et al, 2019).…”
Section: Et-1-reduced Camp In Covid-19supporting
confidence: 53%
“…As well known, mitochondria express α7-nAChR; nicotine in isolated mitochondria decreases the consumption of O 2 and the mitochondrial membrane potential whereas in intact cells the consumption of O 2 , and the Ca 2+ levels increase. The reduction of the mitochondrial membrane potential is linked to ATP reduction [ 92 ]. High levels of cytosolic Ca 2+ concentrations and influx of Ca 2+ into mitochondria sustain viral replication of different respiratory viruses such as RSV, MV RV [ 98 ], and SARS-CoV [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…chain and leak of electrons from electron chain and induce oxidative stress by generating ROS that is capable to target several intracellular components including mtDNA. While there is evidence of a substantial increase in oxidative stress attributed to exposure to cigarette smoke, [26,27] there is a limited investigation concerning the impact of cigarette smoke on the mtDNA content especially in disease-free individuals. In our study, cigarette smoking was negatively associated with mitochondrial DNA copy number, but it was not statistically significant likely due to small sample size.…”
Section: Discussionmentioning
confidence: 99%